A robust asymptotic tracking controller for an uncertain 2DOF underactuated mechanical system motivated by a satellite attitude control problem - Emirsajłow, Zbigniew; Barciński, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
The paper is devoted to the theoretical problem of designing a robust asymptotic tracking control system for a rotational motion of a 2DOF underactuated linear mechanical system with parametric uncertainties. The mathematical formulation of the problem is motivated by the attitude control problem of an earth observation satellite with a solar panel. It is assumed that all the parameters of the plant model are uncertain and the plant single input is additively disturbed by an unknown constant torque.
Keywords: underactuated 2DOF mechanical system; rotational motion control; robust asymptotic tracking; robust error feedback controller